Human Factors and Ergonomics in Telehealth Interfaces: Enhancing Patient Engagement and System Usability (Digital Health & Telemonitoring Advances E: 3117-6461 | P: 3117-647X, 2026)
The rapid expansion of telehealth technologies has transformed healthcare delivery by enabling remote consultation, monitoring, and intervention. However, the effectiveness of telehealth systems is highly dependent on user interaction, usability, and patient engagement. Human factors and ergonomics (HFE) play a critical role in designing telehealth interfaces that are intuitive, accessible, and efficient for diverse user populations. This paper presents a comprehensive analysis of human-centered design principles in telehealth interfaces, focusing on enhancing patient engagement and system usability. The study examines key ergonomic factors, including cognitive load, interface design, accessibility, and user experience (UX), and their impact on telehealth adoption and effectiveness. It explores the integration of usability engineering, behavioral science, and AI-driven personalization to optimize user interaction. Furthermore, the paper evaluates common usability challenges in telehealth systems, such as interface complexity, digital literacy barriers, and lack of standardization. Through a multidisciplinary perspective, this research highlights design strategies that improve patient satisfaction, adherence, and clinical outcomes. The paper also discusses future directions, including adaptive interfaces, voice-based interaction, and inclusive design frameworks. The findings emphasize that incorporating human factors into telehealth design is essential for creating scalable, user-friendly, and effective digital healthcare systems.